Analisis Pengendalian Kualitas Produk Tempe dengan Menggunakan Metode Statistical Quality Control (SQC): Studi Kasus: UMKM HARTONO Tempe Kabupaten Kebumen - R. Akhmad Zakaria Nur Alim; Rizki Afif Pratama; Alfiansyah Alfiansyah; Widya Setiafindari (Asosiasi Riset Teknik Elektro dan Informatika Indonesia, 2024)
This research was based on a flaw found in observations made during a period of one month with the location object of MSMEs Hartono tempe. The discovery of this defect has an impact on the quality of tempeh so that it can reduce people's purchasing power in tempeh. The purpose of this study is to find out how good the quality of the products produced, find out how big the level of defects in tempeh production is, and find out the causes of product defects using the SQC method. The use of the SQC method is used to control the quality of the initial process of the finished product, as well as certain quality standards that have been agreed upon by the company. Data was collected through interviews with company owners and observations for one month on the tempeh production process that occurred. Data shows that defects in tempeh production include the inclusion of foreign objects, uneven shapes, and damaged packaging. After observation, it turned out that damaged packaging was the most common cause of defects during observations. So, we will make a suggestion, namely making a plastic adhesive device (Sealer). In addition to reducing defects due to damaged packaging, the manufacture of sealers also speeds up the plastic gluing process when producing.